Safety and Effectiveness of 100 mg/kg/day Deferiprone in Patients with Thalassemia Major - Taher, A. (2005)
Deferiprone at a dose of 75 mg/kg/day is not sufficiently effective to maintain iron stores at a level which has been considered safe in all patients with iron overload. Our main aim was to determine the safety of long-term therapy with high-dose (100 mg/kg/day) deferiprone. A secondary aim was to determine the efficacy of this high dose. Twelve thalassemia major patients received deferiprone at a dose of100 mg/kg/day over 2 years. Transient aspartate aminotransferase increase (8 patients), gastrointestinal discomfort (3 patients) and arthralgia (2 patients) were the most commonly reported side effects. None of the patients discontinued therapy. The mean serum ferritin level fell from 3,901 ± 3,618 to 1,790 ± 2,205 µg/l after 2 years (p < 0.05). Five of the 12 patients continued to receive deferiprone for an additional 3 years. No new side effects were encountered. The mean serum ferritin level in this subgroup was initially 2,510 ± 332 µg/l and dropped to 1,511 ± 664 µg/l after 5 years (p < 0.05). Liver iron levels at the end of the 2-year study ranged from 1.0 to 30.9 mg/g dry weight, 3 of the patients having levels above 15 mg/g.